Final answer:
To estimate f(x+h), we use linear approximation which leads to the formula f(x+h) = f(x) + f'(x)(h), simplifying to f(x+h) = a + bh, corresponding to option A.
Step-by-step explanation:
To estimate f(x+h) given that f(x)=a and f'(x)=b, we can use the linear approximation, which is essentially the equation of the tangent line at x. The tangent line's equation at the point (x, f(x)) with slope f'(x) is f(x) + f'(x)(h-x). Since we are estimating f(x+h), we set h as the difference between x+h and x. Simplifying the equation, we get:
f(x+h) = f(x) + f'(x)(h-x)
But since x is our initial point, h-x simplifies to just h. So we have:
f(x+h) = a + bh
This corresponds to option A) f(x+h) = a + bh.